2015
DOI: 10.1017/s1751731115000877
|View full text |Cite
|
Sign up to set email alerts
|

Access to shade changes behavioral and physiological attributes of dairy cows during the hot season in the subtropics

Abstract: The effect of shade on behavior and physiological attributes of grazing cows in a high altitude subtropical zone is not well established. This work aimed to investigate how social and ingestive behaviors, as well as physiological and other attributes of dairy cows such as milk production, change in a subtropical environment during the hot season either with or without free access to shade. Fourteen lactating cows were kept on pasture either with no shade or with free access to shade for 5 days and their behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 24 publications
2
40
0
1
Order By: Relevance
“…In the present study, the increased proportion of time spent standing up of the SH2 group compared with SH10 is probably linked to the attempt to increase body surface exposed to air and facilitate heat dissipation (Palacio et al, 2015), as SH2 cows spent less time in shade and were exposed to solar radiation during an extended time compared with SH10 cows, confirming previous results of Schütz et al (2010) and of Vizzotto et al (2015), who reported that cows without access to shade increased time spent standing compared with those with access the shaded area. Kendall et al (2006) evaluated the behaviour of dairy cows with 1.8 m² of shade or without shade and also noted the preference of cows to remain standing in the shade.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, the increased proportion of time spent standing up of the SH2 group compared with SH10 is probably linked to the attempt to increase body surface exposed to air and facilitate heat dissipation (Palacio et al, 2015), as SH2 cows spent less time in shade and were exposed to solar radiation during an extended time compared with SH10 cows, confirming previous results of Schütz et al (2010) and of Vizzotto et al (2015), who reported that cows without access to shade increased time spent standing compared with those with access the shaded area. Kendall et al (2006) evaluated the behaviour of dairy cows with 1.8 m² of shade or without shade and also noted the preference of cows to remain standing in the shade.…”
Section: Discussionsupporting
confidence: 90%
“…Our results agree with those reported by Schütz et al (2010), in which cows with access to 9.6 m 2 of shade per cow spent more than twice as much time in the shade than cows with 2.4 m 2 of shade per cow. Previous studies evidenced that during the warm season, lactating dairy cows seek shade (Schütz et al, 2008(Schütz et al, , 2010(Schütz et al, , 2014Vizzotto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinkers may also be useful for monitoring social competition. During periods of elevated ambient temperature when cows increase water intake and decrease feed intake (Kadzere et al, 2002), aggressive interactions are high (Coimbra et al, 2012), resulting in more competition at and close to the water source (Vizzotto et al, 2015). Especially during heat stress, water is an important resource for dairy cows, and competition can result in dominant animals preventing subordinate animals from access (Coimbra et al, 2012).…”
Section: Technical Notementioning
confidence: 99%
“…Two of the observation periods were assigned as the baseline set (mean ± SD ambient temperature = 18.9 ± 3.8°C; range = 12.9-25.4°C) and used to identify the optimal interval; the 2 other periods were assigned as the validation set (mean ± SD ambient temperature = 20.5 ± 4.7°C; range = 13.9-29.3°C) and thus used to validate the interval. As elevated ambient temperatures affect competitive behavior at the drinker (Vizzotto et al, 2015), the 24-h observation periods were assigned to either the baseline set or the validation set based on mean daily temperature. The baseline set comprised the more moderate 2 d (mean ± SD ambient temperature = 18.3 ± 3.9 and 19.5 ± 3.7°C for baseline set periods 1 and 2, respectively), and the validation set comprised the warmest and coolest days (mean ± SD ambient temperature = 24.0 ± 3.6 and 16.9 ± 2.2°C for validation sets 1 and 2, respectively).…”
Section: Technical Notementioning
confidence: 99%